PENGARUH KARAKTERISTIK PERUSAHAAN, LEVERAGE, DAN OPINI AUDIT TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR MANUFAKTUR SELAMA MASA PANDEMI - Musa Fahmuddin Irham; Adam Zakaria; Tri Hesti Utaminingtyas (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to examine the influence of firm characteristics, leverage, and audit opinion on profitability in the manufacturing sub-sector companies during the pandemic period listed on the Indonesia Stock Exchange. The sample selection technique employed purposive sampling using a quantitative approach with secondary data obtained from financial reports of manufacturing sub-sector companies listed on the Indonesia Stock Exchange during the 2020-2021 period. The data analysis technique used to test the hypotheses was regression analysis. The results of this study indicate that: (1) Firm characteristics, measured by company size and age, have a positive influence on profitability. (2) Leverage, measured by the debt-to-equity ratio, has a positive influence on profitability. (3) Audit opinion has a negative influence on profitability. Suggestions for future research include expanding the scope of the study by using data from a longer period or extending the research to companies outside the manufacturing sub-sector